A behavioral genetic study of trait emotional intelligence - Vernon, Philip A. (Array, 2008)
Numerous models of emotional intelligence (EI) have proposed the existence of hitherto undiscovered mental abilities, competencies, and skills. The theory of trait emotional intelligence suggests that the content domains of these models invariably contain permutations of personality traits. The two studies in this article examine the heritability of trait EI scores with a view to demonstrating empirically that the construct has a similar level of genetic influence as other personality traits. Study 1 was a family design of 133 high-school students and their parents. Regressions of offspring on midparent scores suggested median upper-limit heritability estimates of .18 at facet level, .25 at factor level, and .32 at the global trait EI level. Study 2 was a twin design (213 pairs of monozygotic [MZ] twins and 103 pairs of dizygotic [DZ] twins). It yielded median heritabilities of .42 for the facets, .44 for the factors, and .42 for global trait EI. Overall, our findings are in accordance with studies of the major personality dimensions and provide further empirical support for the conceptualization of EI as a personality trait.